The role of fish ponds in the nutrient dynamics of mixed farming systems - Muendo, Patricia Nduku (My University, 2006)
Rapid population growth in developing countries has resulted in increased demand for food, leading to increased pressure to extend land under cultivation and to intensify food production. Because most of the arable land has already been utilized, further intensification of agricultural production has involved conversion of marginal lands such as forest reserves, communal grazing lands and fragile areas such as river banks and steep hill slopes. Intensified crop production on marginal lands enhances the risk for soil degradation, like soil fertility decline. In many situations, inorganic fertilizers are not available or are too expensive, and efficient utilization of organic residues such as crop residues and manures is constrained by a temporal mismatch between availability and application. Diversification of farming activities potentially increases nutrient efficiencies. One promising additional activity is aquaculture and the development of integrated aquaculture - agriculture (IAA) systems. Although integrated aquaculture – agriculture farming systems have been developed and practiced in some parts of Asia, they have not been widely adopted. In many developing countries, especially in Africa, aquaculture itself is still poorly developed. Aquaculture is considered separately from agriculture and its benefits are measured in terms of fish production, ignoring its role in nutrient cycling through integrated farming systems. Yet, the majority of nutrients entering ponds, including fertilizers, feeds and nutrients contained in inflows from channels or run-off from watersheds, accumulate in the sediment. These nutrients are a potential nutrient source for terrestrial agriculture. This thesis explored the use of fish ponds as nutrient traps (besides fish production) to increase the nutrient use efficiency in mixed farming systems. Focus was put on (i) nutrient utilization efficiency of agricultural by-products such as crop residues and animal manure in aquaculture production, and(ii) in quantitative aspects of sediment and nutrient accumulation in aquaculture ponds, and pond sediments’ potential as a fertilizer in landbased agriculture